PENGEMBANGAN ALAT PERAGA PEMELAJARAN MATEMATIKA KELAS III SD BERBASIS METODE MONTESSORI DI SD ISLAM ASSALAM CURUG KABUPATEN TANGERANG - Fita nur septiana (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2022)
PENGEMBANGAN ALAT PERAGA PEMBELAJARAN MATEMATIKA KELAS III SD BERBASIS METODE MONTESSORI DI SD ISLAM ASSALAM CURUG KABUPATEN TANGERANG Fita Nur Septiana1, Mawardi, S.Si., M.Pd2, Najib Hasan, M.Pd3 1Program Studi Pendidikan Guru Sekolah Dasar 1,2 Universitas Muhammadiyah Tangerang E-mail : fitanurseptiana97@gmail.com(1) Wardi.elmawardi@gmail.com (2) Najibhasanbay@gmail.com (3) Abstract : the purpose of this study is to develop model multiplication boards based on montessori methods in math class III . The research USE addie's version of development models. The population in this study is 3rd graders a islamic elementary school assalam curug. The techniques in drawing samples in the study use the small group test of 10 students and the large group test of 16 students. The instruments used include interviews, angkets and pre-test questions. The results of this development study met the